A Rare Case; Bilateral Sudden Sensorineural Hearing Loss - Kuzu M.D., Selçuk (International Journal of Innovative Research in Medical Science, 2017)
Sudden hearing loss (SHL) first appeared in the literature with the definition of deKlein in 1944. Sudden hearing loss is defined as hearing loss in the sensorineural component over 30 decibels (dB) holding at least 3 consecutive frequencies that occur within 72 hours. Bilateral sudden sensorineural hearing loss is a rarely seen condition requiring specific treatment and corresponds to 0.44-4.9% of all sudden sensorineural hearing loss patients. In this study, we aimed to present a case of bilateral sudden loss of hearing loss, possibly after a previous upper respiratory tract infection, and to present it in the light of current literature.